A secondary analysis to understand the views and perceptions of what older people consider constitutes a 'good death' - Winfield, Hannah (2009)
The ageing of populations is the current demographic trend. Death now most commonly occurs within older age, and yet there remains a deficiency of research involving those for whom this experience affects most; older people.